Editorial. Issue 4 (1st December 2014) - Wilkinson, Nicholas
Abstract : This issue has many manuscripts dealing with PLACE, GENTRIFICATION PROCESSES, HOME OWNERSHIP, VERTICAL GREENERY SYSTEMS, SUSTAINABLE PERFORMANCE OF BUILDINGS AND COMMUNICATION IN PRACTICES.